Study guides

☆☆

Q: What is 2x equals 3y if x is 7 and 6 is y?

Write your answer...

Submit

Still have questions?

Related questions

Since 2x-3y=4y=8 we can say that 4y=8 therefor y=2 We can also say that 2x-3y=4y and as y=2 2x-6=8 so 2x=14 and x =7 so y=2 and x=7

x + 8y = 3 therefore 2x + 16y = 6 (a) 2x + 3y = -7 (b) Subtract (b) from (a): 13y = 13 so y = 1 and x = -5

7

{-4,-5}

If 2x - 3y = 7, -3 y = 7 - 2x or y = (2x - 7)/3, or y = (2/3)x - (7/3). The slope is 2/3 and the y-intercept is -(7/3).

(5, 1)

X equals 1 and so does Y

1) 2x + 4y = -62) x -3y = 7We can add 3y to both sides of equation 2) to getx = 3y + 7Now we can substitute 3y + 7 for x in equation 1).In other words, we replace any 'x'es in equation 1) with 3y + 7.2x is two times x, so this becomes 2(3y + 7) which is two times 3y_and_sevenEquation 1) becomes2(3y + 7) + 4y = -6or6y + 14 + 4y = -6or10y + 14 = -6Subtracting 14 from both sides,10y = -20Dividing both sides by 10,y = -2.Substituting -2 for y in equation 1),2x - 8 = -6Add 8 to both sides2x = 2x = 1Check our results with equation 2x - 3y = 71 + 6 = 7

7--

2x-6=7, x=?

I meant 2x+6

It is the equation of a line in 3-dimensional space.

2x - 3y = 7 -37 + y = 7 The second equation simplifies to -2y = 7 so that y = -7/2 Substituting this value for y in the first equation gives 2x - 3*(-7/2) = 7 2x + 21/2 = 7 or 4x + 21 = 14 so that 4x = -7 and so x = -7/4 So the solution to the given question is (x, y) = (-7/4, -7/2)

-3y + 6 = 7 Therefore, -3y = 1 Therefore, y = 1/-3 Therefore, y = -0.3 recurring (that is, -0.3333...)

2x - 3y = -4 3x + 2y = 33 Eqn(1)*2: 4x - 6y = -8 Eqn(2)*3: 9x + 6y = 99 Add the eqns: 13x = 91 so that x = 7 Substitute in eqn1: 14 - 3y = -4 so that 18 = 3y or y = 6 SOLUTION: x = 7, y = 6

Stating that it is an equilateral triangle, we are told that all sides are equal.This is another way of saying:4x - y = 7and2x + 3y = 7So this can be solved by eliminating one of those variables:2x + 3y = 7x = (7 - 3y) / 24((7 - 3y) / 2) - y = 714 - 7y = 7y = 1x = 2

10x+2x-3y-4y=12x-7y

x=7

Multiply First equation by 2: 6y - 2x = 0Add second equation to this: 6y - 2x + 2x + 2y = 0 + 7Simplify: 8y = 7 so y = 0.875 and x = 2.625

2x + 7 = 1 Therefore, 2x = -6 x = -6/2 x = -3

- 7/5

7

4x - 7 = 2x + 5 2x - 7 = 5 2x = 12 x = 6.

(A): 4x + y = 7 (B): 2x - 3y = -7 2*(B) 4x - 6y = -14 Subtract from (A) 7y = 21 Divide both sides by 7: y = 3 Substitute in (A): 4x + 3 = 7 ie 4x = 4 or x = 1 Answer: x = 1 , y = 3

8x-7 plus 2x equals 6 plus 5x plus 2?